A Novel Linelet-Based Representation for Line Segment Detection - Nam-Gyu Cho; Yuille, Alan; Seong-Whan Lee (IEEE transactions on pattern analysis and machine intelligence, 2018)
This paper proposes a method for line segment detection in digital images. We propose a novel linelet-based representation to model intrinsic properties of line segments in rasterized image space. Based on this, line segment detection, validation, and aggregation frameworks are constructed. For a numerical evaluation on real images, we propose a new benchmark dataset of real images with annotated lines called YorkUrban-LineSegment. The results show that the proposed method outperforms state-of-the-art methods numerically and visually. To our best knowledge, this is the first report of numerical evaluation of line segment detection on real images.